Screw Torque and Interfragmentary Compression in Equine Cadaver Longbone Fractures - Field, J. R. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
The purpose of the study was to determine what contribution individual surgeon, location and bone type made to the optimal applied screw torque (Mopt) for interfragmentary compression of equine cadaver long-bone fractures. Four surgeons were required to insert 4.5 mm fully-threaded cortical bone screws at several locations in both third metacarpal and third metatarsal bones.Consideration of individual differences was significant (P <0.05) as was location (P <0.05). There did not appear to be a contribution to variability through bone type.Torque was also measured at point-of-failure (Mmax) showing no relationship to individual or location.This study examines the effect of different individuals, location and bone type on the perceived optimal torque for interfragmentary compression of equine longbone fractures. It was found that individuals and location significantly effected the perceived optimal applied torque. This suggest that, for mature equine longbone fractures, the use of torque limiting devices may be a consideration to optimize interfragmental compression.
Keywords: Torque; screws; bone